2011
DOI: 10.1037/a0022874
|View full text |Cite
|
Sign up to set email alerts
|

Cohort differences in Big Five personality factors over a period of 25 years.

Abstract: The notion of personality traits implies a certain degree of stability in the life span of an individual. But what about generational effects? Are there generational changes in the distribution or structure of personality traits? This article examines cohort changes on the Big Five personality factors Extraversion, Agreeableness, Conscientiousness, Neuroticism, and Openness to Experience, among first-year psychology students in The Netherlands, ages 18 to 25 years, between 1982 and 2007. Because measurement in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
66
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 67 publications
9
66
2
Order By: Relevance
“…The trends in personality are also similar across levels of cognitive ability and across demographic subgroups. Our results on traits related to extraversion (i.e., sociability and activity-energy) are consistent with studies reporting increasing levels of extraversion (16,(24)(25)(26). Our findings for conscientiousnessrelated traits are in agreement with findings from freshman psychology students at the University of Amsterdam between 1982 and 2007 (25) and from the Baltimore Longitudinal Study of Aging between 1989 and 2004 (43).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The trends in personality are also similar across levels of cognitive ability and across demographic subgroups. Our results on traits related to extraversion (i.e., sociability and activity-energy) are consistent with studies reporting increasing levels of extraversion (16,(24)(25)(26). Our findings for conscientiousnessrelated traits are in agreement with findings from freshman psychology students at the University of Amsterdam between 1982 and 2007 (25) and from the Baltimore Longitudinal Study of Aging between 1989 and 2004 (43).…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, the selectivity of college admissions has changed over time, which has changed the composition of college student populations by socioeconomic backgrounds (22,23). There are some studies where the same personality test was given to different cohorts of the same source population at the same age (24)(25)(26)(27), but generalizing their findings to wider populations is problematic due to self-selection of survey respondents (19,20). On the other hand, researchers have used large and representative data on high school seniors in the United States.…”
mentioning
confidence: 99%
“…While the term trait conveys the conceptualization of personality as stable, it is known that personality scores change over the lifespan (McCrae et al, 1999;Soto et al, 2011) and between cohorts (Smits et al, 2011). A meta-analysis of longitudinal studies revealed that the mean score of neuroticism decreases between age 12 and 40 years, and remains largely stable thereafter (Roberts et al, 2006).…”
mentioning
confidence: 99%
“…The 5PFT consists of five scales, each including 14 items measured with 7-point Likert scales. The data were obtained from Smits, Dolan, Vorst, Wicherts, and Timmerman (2011), and were collected in a sample of first-year psychology students in the Netherlands between 1982 and 2007. Smits et al (2011) demonstrated that the 5PFT dimensions correspond to the five dimensions of the NEO PI (Costa & McCrae, 1985).…”
Section: Illustration Datamentioning
confidence: 99%